Weaver and Devore general store -- photograph ... - Seale, Linda N. (University of Alberta Library, 1965)
Weaver and Devore general store beside Back Bay, Old Town, Yellowknife, NT, September 1965. Suppliers of outfits for trappers and prospectors. Now re-located to an adjacent building the old building in use as a restaurant (2001) ...